Development Policies and Policy Processes in Africa Modeling and Evaluation - Henning, Christian; Badiane, Ousmane; Krampe, Eva (Advances in African Economic, Social and Political Development, 2017)
economics; quantitative policy evaluation; Comprehensive Africa Agriculture Development Programme (CAADP); poverty